Effectiveness of Meta Cognitive Interpersonal Approach Training on Rumination and Self-Esteem in Betrayed Women - Mohammad Mohammadipour; Zahra Montajabian; Sajjad Mohammadipour (پژوهش‌های کاربردی روانشناختی)
The aim of the present study was to investigate the effectiveness of meta cognitive interpersonal approach training on rumination and self-esteem in women who had been betrayed. The research design and purpose of this study were the foundation for the quasi-experimental and pretest-posttest methodology, which included a control group. The statistical population of the research consisted of all the women who visited the counseling clinic in Isfahan in 2021 as a result of their husband's infidelity. A sample of 30 individuals was selected based on the study's eligibility criteria and subsequently divided into two experimental and control groups of 15 individuals each. Before and after the intervention, participants completed the Ruminative Response Scale (RS) and Rosenberg’s Self-Esteem Scale (RSES). Subsequently, the experimental group was subjected to eight 90-minute sections of meta cognitive interpersonal therapy. Data were analyzed using descriptive statistics (mean and standard deviation) and inferential statistics (multivariate and univariate analysis of covariance) in SPSS-25 software. The analysis revealed that meta cognitive interpersonal approach training resulted in an increase in self-esteem, a decrease in rumination, and a rise in self-esteem in betrayed women. It is suggested that meta cognitive interpersonal approach should be used to reduced rumination and increased self-esteem in betrayed women, in order to improve the mental health of women affected by marital infidelity.